End-stage renal disease in Canada: prevalence projections to 2005 - Schaubel, D E; Morrison, H I; Desmeules, M; Parsons, D A; Fenton, S S (Canadian Medical Association journal (CMAJ), 1999)
The incidence and prevalence of end-stage renal disease (ESRD) have increased greatly in Canada over the last 2 decades. Because of the high cost of therapy, predicting numbers of patients who will require dialysis and transplantation is necessary for nephrologists and health care planners. The authors projected ESRD incidence rates and therapy-specific prevalence by province to the year 2005 using 1981-1996 data obtained from the Canadian Organ Replacement Register. The model incorporated Poisson regression to project incidence rates, and a Markov model for patient follow-up. Continued large increases in ESRD incidence and prevalence were projected, particularly among people with diabetes mellitus. As of Dec. 31, 1996, there were 17,807 patients receiving renal replacement therapy in Canada. This number was projected to climb to 32,952 by the end of 2005, for a relative increase of 85% and a mean annual increase of 5.8%. The increased prevalence was projected to be greatest for peritoneal dialysis (6.0% annually), followed by hemodialysis (5.9%) and functioning kidney transplant (5.7%). The projected annual increases in prevalence by province ranged from 4.4%, in Saskatchewan, to 7.5%, in Alberta. The projected increases are plausible when one considers that the incidence of ESRD per million population in the United States and other countries far exceeds that in Canada. The authors predict a continued and increasing short-fall in resources to accommodate the expected increased in ESRD prevalence.